The Dual Role of STAT1 in Ovarian Cancer: Insight Into Molecular Mechanisms and Application Potentials - Li, Xin; Wang, Fanchen; Xu, Xiaolin; Zhang, Jinguo; Xu, Guoxiong (Frontiers in Cell and Developmental Biology, 2021)
The signal transducer and activator of transcription 1 (STAT1) is a transducer protein and acts as a transcription factor but its role in ovarian cancer is not completely understood. Practically, there are two-faced effects of STAT1 on tumorigenesis in different kinds of cancers. Existing evidence reveals that STAT1 has both tumor-suppressing and tumor-promoting functions involved in angiogenesis, cell proliferation, migration, invasion, apoptosis, drug resistance, stemness, and immune responses mainly through interacting and regulating target genes at multiple levels. The canonical STAT1 signaling pathway shows that STAT1 is phosphorylated and activated by the receptor-activated kinases such as Janus kinase in response to interferon stimulation. The STAT1 signaling can also be crosstalk with other signaling such as transforming growth factor-β signaling involved in cancer cell behavior. Ovarian cancer is often diagnosed at an advanced stage due to symptomless or atypical symptoms and the lack of effective detection at an early stage. Furthermore, patients with ovarian cancer often develop chemoresistance and recurrence. This review focuses on the multi-faced role of STAT1 and highlights the molecular mechanisms and biological functions of STAT1 in ovarian cancer.